2018
DOI: 10.1186/s12263-018-0620-8
|View full text |Cite
|
Sign up to set email alerts
|

Food intake biomarkers for apple, pear, and stone fruit

Abstract: Fruit is a key component of a healthy diet. However, it is still not clear whether some classes of fruit may be more beneficial than others and whether all individuals whatever their age, gender, health status, genotype, or gut microbiota composition respond in the same way to fruit consumption. Such questions require further observational and intervention studies in which the intake of a specific fruit can be precisely assessed at the population and individual levels. Within the Food Biomarker Alliance Projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 95 publications
0
35
0
Order By: Relevance
“…Coumarins are lactones derived from hydroxycinnamic acids, a flavonoid, [ 37,38 ] , which are well‐documented in many plant‐based foods including apples. [ 39,40 ] A previous study reported that plasma concentrations of hydroxycinnamic acids (including phloretin and coumaric acid) significantly increased after consumption of 1 kg of apple, peaking between 1–3 h following apple consumption, in a short‐term intervention study. [ 40 ] In this study, the urinary levels of 2,6‐dimethyl‐2‐(2‐hydroxyethyl)‐3,4‐dihydro‐2H‐1‐benzopyran peaked at 4 h following apple consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coumarins are lactones derived from hydroxycinnamic acids, a flavonoid, [ 37,38 ] , which are well‐documented in many plant‐based foods including apples. [ 39,40 ] A previous study reported that plasma concentrations of hydroxycinnamic acids (including phloretin and coumaric acid) significantly increased after consumption of 1 kg of apple, peaking between 1–3 h following apple consumption, in a short‐term intervention study. [ 40 ] In this study, the urinary levels of 2,6‐dimethyl‐2‐(2‐hydroxyethyl)‐3,4‐dihydro‐2H‐1‐benzopyran peaked at 4 h following apple consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Epicatechin sulfate is the sulfate form of epicatechin, a flavonoid, which has multiple plant sources. [ 31,39 ] Methyl(epi)catechin sulfate has previously been associated with apple and pear intake. [ 31 ] When comparing urinary metabolome profiles with data from a 24‐h dietary recall, Edmands et al.…”
Section: Discussionmentioning
confidence: 99%
“…This work aimed to provide an overview of the metabolites found in biological fluids that could potentially act as BFIs for grape and different berry types, further evaluating their validity considering the current available information and identifying the aspects that require further investigation. There are several examples where a single metabolite could be a biomarker of a particular food intake, such as phloretin for apple intake [ 166 ]. However, the composition of each plant food is very complex (from the quantitative and qualitative point of view) and many of the compounds are widely distributed among a variety of foods [ 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate the identification and evaluation of new candidate BFIs, the Food Biomarker Alliance (FoodBAll) [21], a project funded by the Joint Programming Initiative a Healthy Diet for a Healthy Life, established guidelines to conduct a literature search dedicated to food intake biomarkers [25] and to evaluate their level of validation using a set of consensus criteria [26]. The guidelines were applied for all major food groups: fruit and vegetables, meats, fish, and other marine foods, dairy products, cereals and whole grains, alcoholic and non-alcoholic beverages, vegetable oils, nuts, and spices and herbs (http://foodmetabolome.org/wp3) [27][28][29][30][31][32][33][34][35][36]. The present article presents the results of the in depth exploration of possible biomarkers of intake for green leafy vegetables (lettuce, spinach, endive, and garden rocket) as well as bulb and stem vegetables (artichoke, asparagus, celery).…”
Section: Introductionmentioning
confidence: 99%